Investing abroad from the bottom of the productivity ladder: BRICS multinationals in Europe - Marco Sanfilippo (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
This paper analyses differences in total factor productivity and other competitiveness indicators of emerging multinationals (EMNEs) from Brazil, Russia, India, China and South Africa (BRICS) against their counterparts from developed countries and domestic MNEs. The current literature suggests that early internationalisation strategies by EMNEs are characterised by a lack of experience in diverse economic and cultural contexts and are explicitly driven by asset-exploration strategies. If true, this should translate into significant differences in performance, especially when they invest in developed countries. Based on a large database on foreign affiliates in Europe, results find EMNEs at the bottom of the productivity ladder, with a productivity gap around 20-30 percentage points compared to more established competitors. Moreover, the paper points to high heterogeneity among EMNEs that affects their relative performance according to their current levels of productivity or to differences in their sectorial and geographic patterns.
URN:NBN:fi:bof-201408072091
Keywords: F21; F23; 330; emerging market multinationals; total factor productivity; foreign direct in-vestment